2004
DOI: 10.1149/1.1776590
|View full text |Cite
|
Sign up to set email alerts
|

High Capacity SiO[sub 2]-Graphite Composite Electrodes with Chemically Incorporated Metal MHCFs for Electrochemically Switched Alkaline Cation Exchange

Abstract: Bulk metal hexacyanoferrate ͑MHCF͒ has been synthesized within the porous microstructure of conductive composite materials using a simple chemical procedure. The composite materials consist of micrometer-size graphite particles encapsulated in a SiO 2 solid matrix using a sol-gel technique. A strong electrochemical signal from the chemically treated composites is associated with electrochemically switched alkaline-cation exchange. The exchange capacity of these composite electrodes exceeds by more than two ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that they exhibit high conductivity, high electrocatalytic activity for many redox reactions, and resistance to surface fouling. Additionally, they can remain stable in organic solvents for a relatively long time (several hours), perform at lower overpotentials, and are reusable [23]. Adding to the aforementioned advantages, the ease of manufacturing, the lower cost, and the possibility of chemical modification make the G-SiO 2 film electrodes even more appealing [24].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that they exhibit high conductivity, high electrocatalytic activity for many redox reactions, and resistance to surface fouling. Additionally, they can remain stable in organic solvents for a relatively long time (several hours), perform at lower overpotentials, and are reusable [23]. Adding to the aforementioned advantages, the ease of manufacturing, the lower cost, and the possibility of chemical modification make the G-SiO 2 film electrodes even more appealing [24].…”
Section: Introductionmentioning
confidence: 99%
“…In general, inorganic materials are superior to organic ones in the treatment of radioactive liquid waste, due to their higher radiation stability. Recently, nickel hexacyanoferrate (NiHCF) has received special attention because of its excellent affinity for cesium ion (Cs + > Rb + > K + > Na + > Li + ) [16][17][18]. In our laboratory, electroactive NiHCF films have been successfully bound to porous three-dimensional carbon felt (PTCF) substrates by a repetitious batch chemical deposition method [19].…”
Section: Introductionmentioning
confidence: 99%
“…Nanocomposite thin films have numerous applications, including optoelectronic devices, [1,2] photonic devices, [3] protective coatings, [4] electrocatalysis, [5,6] photovoltaic cells, [7] high-k dielectrics, [8] optical isolators, [9,10] sensors, [11][12][13][14][15][16][17] ferromagnetic composites, [18] electrodes, [19] and various other electrical and optical applications. [20,21] A majority of these materials are fabricated using wet-processing techniques.…”
Section: Introductionmentioning
confidence: 99%